PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN KOMPENTENSI TERHADAP KINERJA ASN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI INSPEKTORAT DAERAH KABUPATEN SITUBONDO - Yulianto, Heru; Sari, Lita Permata; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study is to analyze the influence of variablesLeadership Style, Communication, and ASN Performance Competence Through Job Satisfaction as an Intervening Variable in the Situbondo Regency Regional Inspectorate. Using the Partial Least Square (PLS) Structural Equation Model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application, Leadership style has a significant positive effect on ASN job satisfaction, Communication has a significant positive effect on ASN job satisfaction, Competence has a significant positive effect on ASN job satisfaction, Leadership style has a significant positive effect on ASN performance, Communication has a positive but not significant effect on ASN performance, Competence has a significant positive effect on ASN performance, ASN job satisfaction has a significant positive effect on ASN performance, Leadership style has a significant positive effect on ASN performance through ASN job satisfaction, Communication has a significant positive effect on ASN performance through ASN job satisfaction and Competence has a significant positive effect on ASN performance through ASN job satisfaction.